Gender Gaps in Cognitive and Non-Cognitive Skills in Early Primary Grades : Evidence from Rural Indonesia - Nakajima, Nozomi; Jung, Haeil; Pradhan, Menno; Hasan, Amer; Kinnell, Angela; Brinkman, Sally (World Bank, Washington, DC, 2016)
This paper examines gender gaps in cognitive and non-cognitive skills among a sample of more than 10,000 children between the ages of 6 and 9 in rural Indonesia. In terms of cognitive skills, the analysis finds evidence of gender gaps favoring girls at each age in test scores of language (0.158-0.252 standard deviations) and mathematics (0.155-0.243 standard deviations) in the early years of primary school. Girls also perform significantly better than boys in non-cognitive skills, with higher scores on the social competence (0.086-0.247 standard deviations) and emotional maturity domains (0.213-0.296 standard deviations) of the Early Development Instrument, a finding consistent with research from high-income countries. Decomposition analyses are used to investigate the extent to which enrollment patterns in preschool and primary school as well as parenting practices contribute to these gender gaps in cognitive and non-cognitive skills. Standard decomposition approaches are extended to correct for selection on observables. The findings show that gender differences in enrollment patterns play a role in explaining gender gaps in test scores, while differences in parenting practices do not. However, the relative contribution of observed factors to gender gaps depends on the available quality of preschool services in the child’s village and whether the outcome of interest is cognitive or non-cognitive skills.